2021
DOI: 10.1038/s41598-021-82181-9
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA gene-based microbiome analysis identifies candidate bacterial strains that increase the storage time of potato tubers

Abstract: In the past, the potato plant microbiota and rhizosphere have been studied in detail to improve plant growth and fitness. However, less is known about the postharvest potato tuber microbiome and its role in storage stability. The storage stability of potatoes depends on genotype and storage conditions, but the soil in which tubers were grown could also play a role. To understand the ecology and functional role of the postharvest potato microbiota, we planted four potato varieties in five soil types and monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Another great concern about the application of the stress-related phytohormone ABA for the induction of pigment and lipid synthesis lies within its possible impact on the host-associated bacteria, which are known to play a crucial part in microalgal culture stability and productivity [ 95 ]. For the agricultural plants, it was shown that stress conditions highly affect microbial composition of the rhizosphere [ 96 , 97 ]. On the other hand, phytohormones are able to not only positively affect plant physiological state, but also stimulate certain bacterial genera in the microbiome of the roots of higher plants, as a putative carbon source.…”
Section: Discussionmentioning
confidence: 99%
“…Another great concern about the application of the stress-related phytohormone ABA for the induction of pigment and lipid synthesis lies within its possible impact on the host-associated bacteria, which are known to play a crucial part in microalgal culture stability and productivity [ 95 ]. For the agricultural plants, it was shown that stress conditions highly affect microbial composition of the rhizosphere [ 96 , 97 ]. On the other hand, phytohormones are able to not only positively affect plant physiological state, but also stimulate certain bacterial genera in the microbiome of the roots of higher plants, as a putative carbon source.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a significant difference in tuber bacterial communities was observed between the two genotypes during dormancy (the second and third storage periods), indicating the continuous dynamics of bacterial communities during dormancy. Interestingly, changes in microbial communities observed during the storage of potatoes and sugar beets are independent of crop genotypes ( Kusstatscher et al, 2019 ; Buchholz et al, 2021 ). This result is not quite consistent with our findings, which may be attributed to the differences in carbohydrates or a selective relationship between bacterial communities and carbohydrates due to the chemical specificity of fructans.…”
Section: Discussionmentioning
confidence: 99%
“…Tuber crops develop and mature in the soil, and microorganisms on the surface of the tuber during this process have a distinct relationship with the environment. In particular, microorganisms attached to the surface of root crops have been observed, including Staphylococcus , Pseudomonas , and Actinobacteria ( Buchholz et al, 2019 , 2021 ; Shi et al, 2019 ). This finding is consistent with the microbial species on the surface of the JA tubers during storage herein, which may be attributed to the wide distribution of these bacteria that genera-level in soils worldwide ( Fierer et al, 2012 ), and thus, is the genus of the most likely taxa that encounter tubers during the developmental stages and beyond ( Nelson, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 They are found in plant tissues, such as fruits, 2 stems, 3 roots, 4 flowers 5 and tubers. 6 The interaction between endophytic bacteria and 3 their host plants is not completely understood. However, many isolates seem to have beneficial effects on their hosts.…”
Section: Introductionmentioning
confidence: 99%